Determination of Anaerobic Capacity - Reliability and Validity of Sprint Running Tests - Corinna Wawer (운동과학, 2020)
PURPOSE A number of physiological diagnostics were developed. However, the timeline-related diagnostics of maximal anaerobic glycolytic capacity remain unclear. The objective of this study was to evaluate the reliability and validity of a sprint running test to assess the anaerobic capacity. METHODS The study was divided into three parts. Sixty-one male (24±4 years, 181.0±4.3 cm; 78.5±5.9 kg) and twelve female (25±3 years, 167.0±0.6 cm, 60.4±5.7 kg) sports students participated in this study. Twenty-five subjects (13 males, 24±2 years, 181.0±0.5 cm, 78.5±5.9 kg; 12 females, 25±3 years, 167.0±0.6 cm, 60.4±5.7 kg) performed incremental step tests at running track and several linear sprints on a running track (LSRT) with different time durations (8, 10, 12, and 14 seconds)(part I) on different days. Twenty-five male subjects (24±3 years, 180.7±6.7 cm, 84.6±8.8 kg) conducted a 10 or 12 second sprint running on a non-motorized treadmill (NMT)(part II). In part III, twenty-three male subjects (24±2 years, 181.4±5.8 cm, 74.5±7.4 kg) ran a 10 second LSRT and NMT on consecutive days. Capillary blood samplings were taken before (Lacr) and after the sprint running for ten minutes at one minute intervals to find out maximal lactate concentration after exercise and to calculate the maximum lactate production rate (LPRmax). RESULTS For all parts reliability for LPRmax was proven (Part I: 8 seconds: ICC: r=.89; 10 seconds: ICC: r=.82; 12 seconds: ICC: r=.92; 14 seconds: r=.84, respectively; Part II: 10 seconds: ICC: r=.76; 12 seconds: ICC: r=.79). To analyze validity for LPRmax, Part III was conducted and proven valid (ICC: r=.96, p=.074). CONCLUSIONS We demonstrate that LSRT and NMT reliably determine anaerobic capacity and can be used as a valid tool for physiological performance diagnostics.